Motivational factors for a sports ministry: A case study of churches in Pretoria - Tucker, Tim (HTS teologiese studies, 2012)
The purpose of this study was to investigate church leaders’ perceptions of motivational factors for a sports ministry in churches in Pretoria. A survey questionnaire was developed by the researchers to investigate the above perceptions. The survey consisted of demographic questions and perception questions using a structured and a semi-structured questionnaire. The results of the survey were assessed by calculating the significance of each motivational factor for a sports ministry in the church, as perceived by the respondents. Participants were recruited from 32 church leaders from a wide variety of denominational and cultural backgrounds in Pretoria. Results showed that a sports ministry could assist the church in evangelism and fulfilling the Great Commission. Over 95% of all respondents agreed that a sports ministry would have a positive impact on evangelism. The results of the survey showed that the participants from the churches in Pretoria are supportive of a sports ministry as a general strategy to help churches to promote evangelism and outreach, to cross cultural barriers, to keep in touch with society and to provide a place for teaching life skills and develop leaders.